Baby signing 1, 2, 3 : the easy-to-use illustrated guide for every stage and every age - Cadjan, Nancy (Naperville, Ill. : Sourcebooks, 2007)
What if your baby could "talk" to you before he or she could actually speak? This book provides specific signs and techniques for differant age ranges, so you know how to work best with baby at each stage of development.
A developmental look at signing with your child -- Baby sign language dictionary.
Includes bibliographical references (p. [263]-179) and index.
Keywords: Nonverbal communication in infants; Sign language; Infants -- Language; Language acquisition -- Parent participation; American Sign Language